2016
DOI: 10.12688/f1000research.8406.1
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin lactone may improve irritable bowel syndrome with constipation (IBS-C) by inhibiting enzymes in the archaeal methanogenesis pathway

Abstract: Discuss this article AbstractMethane produced by the methanoarchaeon ( Methanobrevibacter smithii M. ) has been linked to constipation, irritable bowel syndrome with smithii constipation (IBS-C), and obesity. Lovastatin, which demonstrates a cholesterol-lowering effect by the inhibition of HMG-CoA reductase, may also have an anti-methanogenesis effect through direct inhibition of enzymes in the archaeal methanogenesis pathway. We conducted protein-ligand docking experiments to evaluate this possibility. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Finally, there is some evidence to suggest that certain statins may have a role in depleting Methanobrevibacter spp., thereby offering a novel therapy for methane-specific SIBO (149, 150). In line with this, a modified-release formulation of lovastatin, termed SYN-010, has been created to deliver the drug in a biphasic manner during transit, thereby avoiding considerable degradation and absorption in the upper gastrointestinal tract (151).…”
Section: Treatmentmentioning
confidence: 99%
“…Finally, there is some evidence to suggest that certain statins may have a role in depleting Methanobrevibacter spp., thereby offering a novel therapy for methane-specific SIBO (149, 150). In line with this, a modified-release formulation of lovastatin, termed SYN-010, has been created to deliver the drug in a biphasic manner during transit, thereby avoiding considerable degradation and absorption in the upper gastrointestinal tract (151).…”
Section: Treatmentmentioning
confidence: 99%
“…63 By the way, methanogenic bacteria may also be targeted using SYN-010, a modified release statin. 64 One study demonstrated that 4 weeks of SYN-010 in IBS patients to reduce methane levels from baseline as well as to improve abdominal pain and stool frequency. 62 The treatment of IBS symptoms may benefit from certain antibiotics, however, antibiotics may even contribute toward the initial onset of IBS symptoms.…”
Section: Mixed Probioticsmentioning
confidence: 99%
“…Several IBS therapeutics have been developed that target the gut microbiota or the secondary consequences of alterations in the gut microbiota ( Table 1 ). 14 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 One of the most well-studied treatments for IBS is the non-absorbable antibiotic rifaximin. Rifaximin is currently available in 47 countries; it has been available in Italy since 1987 and in the United States since 2004.…”
Section: Treatment Of Gut Microbial-related Ibsmentioning
confidence: 99%
“…SYN-010 is a nonabsorbable derivative of the 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitor lovastatin lactone; this modified-release statin formulation is thought to decrease methane production by blocking cell membrane biosynthesis of M. smithii , a predominant methane producer in the GI tract. 53 , 66 , 76 In a phase 2 study, 62 patients with IBS-C and elevated breath methane levels were treated with 4 weeks of SYN-010 21 mg, SYN-010 42 mg, or placebo once daily. 76 After 1 week, only the higher dose of SYN-010 significantly reduced methane levels from baseline ( P =0.047; primary endpoint).…”
Section: Treatment Of Gut Microbial-related Ibsmentioning
confidence: 99%